Identification and Evaluation of Reference Genes for Normalization of Gene Expression in Developmental Stages, Sexes, and Tissues of Diaphania caesalis (Lepidoptera, Pyralidae). Issue 1 (11th January 2020) - Wang, Zheng; Meng, Qianqian; Zhu, Xi; Sun, Shiwei; Liu, Aiqin; Gao, Shengfeng; Gou, Yafeng
Abstract: Diaphania caesalis (Walker) is an important boring insect mainly distributed in subtropical and tropical areas and attacked tropical woody grain crops, such as starchy plants of Artocarpus. Quantitative real-time polymerase chain reaction (qRT-PCR) is a powerful approach for investigating target genes expression profiles at the transcriptional level. However, the identification and selection of internal reference genes, which is often overlooked, is the most vital step before the analysis of target gene expression by qRT-PCR. So far, the reliable internal reference genes under a certain condition of D. caesalis have not been investigated. Therefore, this study evaluated the expression stability of eight candidate reference genes including ACT, β-TUB, GAPDH, G6PDH, RPS3a, RPL13a, EF1α, and EIF4A in different developmental stages, tissues and sexes using geNorm, NormFinder and BestKeeper algorithms. To verify the stability of the recommended internal reference genes, the expression levels of Dcae OBP5 were analyzed under different treatment conditions. The results indicated that ACT, RPL13a, β-TUB, RPS3a, and EF1α were identified as the most stable reference genes for further studies on target gene expression involving different developmental stages of D. caesalis . And ACT and EIF4A were recommended as stable reference genes for different tissues. Furthermore, ACT, EF1α, and RPS3a were ranked as the best reference genes in different sexes based on three algorithms. Our research represents the critical first step to normalize qRT-PCR data and ensure the accuracy of expression of target genes involved in phylogenetic and physiological mechanism at the transcriptional level in D. caesalia .